Sustainable Fabrication of TiO₂ Nanoparticles: For Enhanced Cytotoxicity and Photocatalytic Efficiency - Avinash Ashok Survase; Avdhut Dadaso Kadam; Bandu Shamlal Pawar; Amol Sheshrao Jadhav; Nilesh Tukaram Pandit; Shivangi Shivraj Kanase (The Bioscan, 2025)
Kaas plateau isolated Bacillus halodurans bacteria used for synthesis of TiO2 NPs. The NPs show maximum absorbance at 384 nm. The functional groups of biomolecules play significant role in capping and stabilization of NPs. XRD indicates pure anatase tetragonal crystal nature of NPs. TEM show spherical morphology of TiO2 material having mean diameter 33 nm. Brunauer-Emmett-Teller (BET) indicates a large specific surface area 13.0665 m2/g with mesoporous nature. TiO2 NPs exhibiting 99% degradation performance of diazo dye Red HE3B within 30 min and 92% MDA-MB-231 breast cancer cell growth inhibitory activity. Degradation pathway of Red HE3B was predicted on basis of LC-MS. Phytotoxicity of degraded metabolites showed enhanced growth of seedlings. TiO2 NPs showed enhanced anticancer activity against human breast cancer cell line MDA-MB-231 tumour cells with 56.41 μg/ml IC50 value.